Teaching innovation management in tourism: Learning targets and course contents - Volgger, Michael (2014)
The present paper proposes an integrated understanding of innovation in tourism and presents this integrated understanding as the major building block of innovation management education. It highlights different integration dimensions, ranging from phases to actors, from competences to market trends and from management to governance as well as leadership. Furthermore, the paper suggests an implementation heuristic – the product development cycle – that may enable course participants to translate basic insights about an integrated innovation process into practical endeavours. Hence, overall, the papers promotes an interaction of theory and practice of innovation management, which is perhaps the major target of teaching innovation management in tourism.